ANALYSIS OF SEX-RATIO BY LENGTH CLASS OF BIGEYE TUNA (Thunnus obesus) IN THE INDIAN OCEAN - Bram Setyadji; Andi Bahtiar; Budi Nugraha (Pusbindiklat - LIPI, 2012)
By far the information about Indian Ocean big eye tuna biology and fisheries especially in Indonesia is still verylimited. This paper is an attempt to give some information of the biological observations, especially sex ratio of bigeye tuna(BET) in Indian Ocean. Surveillance was conducted by scientific observers on March–April, 2010 following twocommercial tuna longline vessels based in Port of Benoa. Total 159 of BET managed to be hauled and observed.The result showed that sex ratio of male and female BET was 1:1.12 and study indicated small size (60–100cm) and large size (140–160 cm) of BET comprise of male more than female; while middle size (100–140 cm)dominated by female rather than male. In addition most BET caught were already reached their sexual maturity.